Plant–Soil Feedback: Bridging Natural and Agricultural Sciences - Mariotte, Pierre; Mehrabi, Zia; Bezemer, T. Martijn; De Deyn, Gerlinde B.; Kulmatiski, Andrew; Drigo, Barbara; Veen, G.F. (Ciska); van der Heijden, Marcel G.A.; Kardol, Paul (Trends in ecology & evolution (Amsterdam), 2018)
In agricultural and natural systems researchers have demonstrated large effects of plant–soil feedback (PSF) on plant growth. However, the concepts and approaches used in these two types of systems have developed, for the most part, independently. Here, we present a conceptual framework that integrates knowledge and approaches from these two contrasting systems. We use this integrated framework to demonstrate (i) how knowledge from complex natural systems can be used to increase agricultural resource-use efficiency and productivity and (ii) how research in agricultural systems can be used to test hypotheses and approaches developed in natural systems. Using this framework, we discuss avenues for new research toward an ecologically sustainable and climate-smart future. PSF has been extensively studied in both agricultural and natural systems, with increased activity in recent years, but a framework for integrating the concepts and principles developed in these systems is lacking. Interactions between soil biota and plant leaf and root traits have become an important tool in understanding PSF in wild plants, but this understanding has not yet been utilized in agricultural crop rotations. Soil inoculations with microbial strains are increasingly being used for steering the soil microbiome in agriculture but might also offer a promising method of restoration of degraded systems, and for controlling the spread of invasive species. Increasing evidence shows that PSF can play important roles in mediating ecosystem responses to forecasted climate change and extreme weather events.